1983
DOI: 10.1037/0033-2909.93.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Nonverbal involvement and social control.

Abstract: This article reviews a portion of the research on nonverbal behavior from a functional perspective. Specifically, the focus of this review is the role of nonverbal involvement (e.g., distance, gaze, touch; lean, orientation, paralinguistic cues, facial expression) in the interactive function of social control. The social control function describes a general goal of exercising influence to change the behavior of others. Specifically, that process is designed to produce reactions not likely in the absence of suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
80
0
2

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(83 citation statements)
references
References 106 publications
1
80
0
2
Order By: Relevance
“…LaCrosse (1975) also discovered that affiliative behaviors, similar to those used by Mehrabian and Williams, were more persuasive than nonaffiliative behaviors. In fact, nonverbal behaviors play a significant role in changing attitudes and opinions (Burgoon, Birk, & Pfau, 1990;Edinger & Patterson, 1983;Patterson, 1983). It is the ability of nonverbal involvement cues to function as persuasive tools that makes the investigation of judicial nonverbal communication compelling.…”
Section: Nonverbal Involvementmentioning
confidence: 97%
“…LaCrosse (1975) also discovered that affiliative behaviors, similar to those used by Mehrabian and Williams, were more persuasive than nonaffiliative behaviors. In fact, nonverbal behaviors play a significant role in changing attitudes and opinions (Burgoon, Birk, & Pfau, 1990;Edinger & Patterson, 1983;Patterson, 1983). It is the ability of nonverbal involvement cues to function as persuasive tools that makes the investigation of judicial nonverbal communication compelling.…”
Section: Nonverbal Involvementmentioning
confidence: 97%
“…Social hierarchies are ubiquitous in human societies and successful navigation of the social world implies particular skills to produce and process social cues which reflect, construct or consolidate the vertical dimension of social systems. There is ample evidence that dominance and power are rarely communicated explicitly but mainly expressed through subtle nonverbal cues (Aguinis, Simonsen, & Pierce, 1998;Argyle, Salter, Nicholson, Williams, & Burgess, 1970;Burgoon, 1994;Carli, Martin, Leatham, Lyons, & Tse, 1993;Dovidio & Ellyson, 1982;Dovidio, Ellyson, Keating, Heltman, & Brown, 1988;Edinger & Patterson, 1983;Lee, Matsumoto, Kobayashi, Krupp, & Maniatis, 1992;Mehrabian, 1969Mehrabian, , 1970Mignault & Chaudhuri, 2003;Remland, 1982). It could be shown that culture is influential in molding these nonverbal expressions as well as their perception and cognitive processing (Kowner & Wiseman, 2003;Matsumoto, 2006;Sussman & Rosenfeld, 1982).…”
Section: Introductionmentioning
confidence: 97%
“…Research has shown that nonverbal behaviors can have a significant effect on social interactions and provide information upon which interpersonal judgments are heavily based (Mehrabin & Ferris, 1967;Edinger & Patterson, 1983). In fact, researchers have suggested that nonverbal communications may play the most important role in interpersonal communications (Mehrabian & Ferris, 1967;Edinger & Patterson, 1983) and may account for as much as sixty-five to ninety percent of the total meaning produced in face-to-face communication (de Sola Pool & Schramm, 1976).…”
mentioning
confidence: 97%
“…In fact, researchers have suggested that nonverbal communications may play the most important role in interpersonal communications (Mehrabian & Ferris, 1967;Edinger & Patterson, 1983) and may account for as much as sixty-five to ninety percent of the total meaning produced in face-to-face communication (de Sola Pool & Schramm, 1976). Still, the extent of the role that nonverbal communication plays in interpersonal communications depends, in part, on the context of the interaction itself.…”
mentioning
confidence: 98%